Human rights and development : towards mutual reinforcement - Alston, Philip (O.U.P. OxfordGB, 2005)
Focuses on ways in which the strengths, resources and support of the international human rights, and development communities can be mobilized in order to reinforce one another in their efforts to achieve shared goals.